2012
DOI: 10.1037/a0029542
|View full text |Cite
|
Sign up to set email alerts
|

Inside the practicum in professional psychology: A survey of practicum site coordinators.

Abstract: In recent years, practicum training has become increasingly salient in professional psychology. External practica in particular play a large role in the early, formative experiences of students in training as professional psychologists. The results of this survey of coordinators of external practicum sites {N = 123) give a fresh perspective on how this important work is conducted, building on surveys conducted over 10 years ago, and on a related survey of practicum policies and practices in graduate programs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…A recent North American survey of 123 coordinators of internship style placements at external practicum sites found that, consistent with the argument here, placement "coordinators value their role in training and report that graduate students bring significant benefits to the training setting" (Hatcher, Wise, Grus, Mangione, & Emmons, 2012). However, the authors found cause for concern over limitations in direct clinical observation of student work and suggest this may reflect overall strain upon supervisors and organisations occurring in these real-world settings (Hatcher et al, 2012).…”
Section: Supervisor Experiencesmentioning
confidence: 76%
“…A recent North American survey of 123 coordinators of internship style placements at external practicum sites found that, consistent with the argument here, placement "coordinators value their role in training and report that graduate students bring significant benefits to the training setting" (Hatcher, Wise, Grus, Mangione, & Emmons, 2012). However, the authors found cause for concern over limitations in direct clinical observation of student work and suggest this may reflect overall strain upon supervisors and organisations occurring in these real-world settings (Hatcher et al, 2012).…”
Section: Supervisor Experiencesmentioning
confidence: 76%
“…Where internships are directly linked to academic programs, institutions have the responsibility to ensure placement of interns at appropriate sites and to monitor and evaluate their progress (Lewis et al 2005). They also have to identify appropriate sites and establish working agreements with them as training partners (Hatcher et al 2011(Hatcher et al , 2015(Hatcher et al , 2012. Secondly, education institutions stipulate the qualifications supervisors should possess and delineate the number of hours of supervised clinical activities as well as the total number of hours spent at the counselling internship site (Kaslow et al 2005;Lewis et al 2005).…”
Section: Counsellor Educational Institutionsmentioning
confidence: 99%
“…Secondly, education institutions stipulate the qualifications supervisors should possess and delineate the number of hours of supervised clinical activities as well as the total number of hours spent at the counselling internship site (Kaslow et al 2005;Lewis et al 2005). Counsellor education institutions should work closely with internship sites to address the evaluative nature of supervision by indicating the counselling competencies that interns should acquire at the end of the internship (Hatcher et al 2015(Hatcher et al , 2012. More specifically, training experiences should be appropriate and consistent with education institutions' training goals and objectives (Lewis et al 2005).…”
Section: Counsellor Educational Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review conducted by Sheen, Graj, Pestell, and McGillivray () has demonstrated that psychology students face educational and supervision‐related risk during clinical placement. Educational risk arises from barriers to clinical placement participation including financial difficulties (Bor, Watts, & Parker, ), extended hours (Helmes & Pachana, ), and limited opportunities for direct supervision (Hatcher, Wise, Grus, Mangione, & Emmons, ; Scott, Pachana, & Sofronoff, ). Furthermore, supervision quality can at times be undermined by poor supervisory style or methods of communication (Atkinson & Woods, ; Dodds, ; Gray, Ladany, Walker, & Ancis, ; Nelson & Friedlander, ; Rhinehart, ; Zinkiewicz, ).…”
Section: Introductionmentioning
confidence: 99%